High levels of pretreatment CA125 are associated to improved survival in high grade serous ovarian carcinoma - Morales-Vásquez, Flavia (J Ovarian Res, 2016)
BACKGROUND: Serum levels of CA125 measured before any treatment have been evaluated in epithelial ovarian cancer (EOC) as a predictor of patient survival; however, results in survival index are controversial, as CA125 levels are influenced by several variables. Taking this into consideration, the present study evaluated the association of pretreatment levels of CA125 serum with the clinical stage, histology and differentiation grade of the tumor and the survival rate in a group of patients from an oncology referral center in Mexico, all of them diagnosed with ovarian carcinoma. This retrospective study consisted of 1009 patients with EOC, diagnosed between 2006 and 2013 at the National Cancerology Institute (Instituto Nacional de Cancerología-INCan), considering only those with CA125 measurements before any chemotherapy or surgical cytoreduction. Patients with three years of medical follow-up having pretreatment CA125 value and simultaneous diagnoses of histological subtype, clinical stage and differentiation grade of the tumor (n = 656) were studied in order to determine their survival rate. RESULTS: The abnormal level (>35 U/mL) of CA125 was observed in 99 % of serous carcinoma cases rated I to IV in the FIGO stages. Abnormal CA125 proportions were 89 % in endometrioid subtype and 69 % in mucinous tumors, with the highest absolute value of CA125 observed in serous carcinoma surpassing any other histological subtype. Clinical stages III and IV displayed increased CA125 values compared to stages I and II. Undifferentiated carcinomas show the highest level of this indicator compared with those of low and moderate differentiated grade. Survival evaluation by Kaplan-Meier analysis including only high grade serous carcinoma at FIGO stage III (n = 57) demonstrated 57.1 % chances of survival in patients with CA125 pretreatment levels higher than 500 U/mL. Survival was 26.7 % in patients with CA125 lower than 500 U/mL and the hazard ratio for CA125 ≤ 500 U/mL was 2.28, 95 % CI 1.08–4.84, P = 0.032. CONCLUSIONS: Clinical stage associated with pretreatment absolute values of CA125 should be considered as prognostic factor in EOC patients. Values of CA125 higher than 500 U/mL in high grade serous carcinoma with FIGO stage III resulted in an enhanced survival rate of the patients.